SISTEM KOMUNIKASI LINGKUNGAN PADA PENGELOLAAN SAMPAH TPA TAMANGAPA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI KECAMATAN MANGGALA KOTA MAKASSAR - Husna , Asmaul; Ahdan, Ahdan; Muttaqin Mustari , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study aims to: examine environmental communication in increasing community participation in waste management at TPA Tamangapa and forms of community participation in waste management. The research method used in this research is descriptive qualitative and data collection techniques are observation, interviews, and documentation. This research lasted for one month with 10 (ten) informants, namely the Environment Service staff, TPA Tamangapa officers, and the surrounding community. The results of the study indicate that environmental communication in increasing community participation uses communication strategies in the form of programs such as direct socialization, indirect socialization, and Waste Banks. While the form of community participation is divided into four levels, namely participation in decision making, implementation, utilization of results, and evaluation.